Effect of Gold Nanoparticles on the Structure and Electron-Transfer Characteristics of Glucose Oxidase Redox Polyelectrolyte-Surfactant Complexes - Cortez, María Lorena (2014)
Efficient electrical communication between redox proteins and electrodes is a critical issue in the operation and development of amperometric biosensors. The present study explores the advantages of a nanostructured redox-active polyelectrolyte–surfactant complex containing [Os(bpy)2Clpy]2+ (bpy=2,2′-bipyridine, py= pyridine) as the redox centers and gold nanoparticles (AuNPs) as nanodomains for boosting the electron-transfer propagation throughout the assembled film in the presence of glucose oxidase (GOx). Film structure was characterized by grazing-incidence small-angle X-ray scattering (GISAXS) and atomic force microscopy (AFM), GOx incorporation was followed by surface plasmon resonance (SPR) and quartz-crystal microbalance with dissipation (QCM-D), whereas Raman spectroelectrochemistry and electrochemical studies confirmed the ability of the entrapped gold nanoparticles to enhance the electron-transfer processes between the enzyme and the electrode surface. Our results show that nanocomposite films exhibit five-fold increase in current response to glucose compared with analogous supramolecular AuNP-free films. The introduction of colloidal gold promotes drastic mesostructural changes in the film, which in turn leads to a rigid, amorphous interfacial architecture where nanoparticles, redox centers, and GOx remain in close proximity, thus improving the electron-transfer process.